EBM Tutorial: Introduction to Evidence-Based Medicine (Out of Print) - Keven Jeffery; Lauren Maggio; John Wiecha; Mary Blanchard (Association of American Medical Colleges, 2008)
Abstract Created and maintained by the Boston University Alumni Medical Library, this web-based tutorial designed for self-study can be completed in approximately five minutes and is appropriate to support EBM practice and curricular components. The tutorial was developed as a brief introduction to the basics of EBM in support of literature searching instruction for students in undergraduate medical education. A series of approximately twenty Web pages introduce students to the definition of EBM, types of clinical information resources, the steps in the EBM research process, and the importance of utilizing evidence in medical practice. The tutorial includes a printable search process handout, an interactive map of EBM practitioners, and many self-assessment elements. This tutorial was reviewed by a family medicine physician. Links to related guides and worksheets are provided. This tutorial has worked well as an initial introduction to EBM prior to literature searching workshops.